Analisis SDM Berbasis Kompetensi di Fakultas Ekonomi dan Bisnis: Strategi Mendukung Akreditasi Unggul dan Kurikulum OBE - Akbar, Muhammad Nur Aflah; Srianita, Cindy Catur; Febrianty, Ranisah; Utama, Rony Edward (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In the era of global competition and rapid innovation, higher education institutions are challenged to improve service quality and graduate competencies aligned with industrial demands. This study addresses the critical issue of how competency-based human resources (HR) contribute to achieving excellent accreditation and implementing the Outcome-Based Education (OBE) curriculum. The research was conducted at the Faculty of Economics and Business, Universitas Muhammadiyah Jakarta (FEB UMJ), using a quantitative approach. Data were collected through an online questionnaire involving 60 student respondents from semesters 3 to 7. The results revealed that 83% of respondents agreed or strongly agreed that lecturers delivered materials relevant to industry demands. Additionally, 85% perceived that administrative staff services supported students’ academic processes, and 80% acknowledged the positive contribution of HR performance to educational quality. Furthermore, 78% agreed that lecturers assigned tasks that enhanced students’ competencies, and 76% affirmed that learning processes were aligned with OBE principles. However, 15% of respondents expressed uncertainty or disagreement regarding the consistency of HR competencies and the effectiveness of the learning system, indicating a need for continuous quality improvement. This study concludes that HR at FEB UMJ has significantly contributed to both academic service quality and curriculum development. It recommends ongoing HR development through targeted training and strengthened collaboration to support sustainable academic excellence.